Information de la société et journalisme - Jean Claude Bourret (VertigO, 2003)
It is very difficult for the press to identify and disseminate intelligible information on the water problem and more generally that of the environment.  This is a widely admitted fact, due to the technical character of the vocabulary used; differences in expert opinion about the current and future situation; lack of political will on the part of governments in promoting profound changes in lifestyles as well as the redundancy of declarations and recommendations from succeeding major international conferences. In this context, reporters have an important mission: that of developing responsible citizenship by seeking intelligible and targeted information and of promoting a certain number of values and disseminating them periodically. By informing the public can only help reduce the problems posed by the worldwide water shortage. How to reach this goal? That is one of the objectives of this colloquium on education for water ethic, as informing is educating.